STUDENTS PERSPECTIVE ON ONLINE MEDICAL EDUCATION DURING LOCKDOWN AS A RESULT OF COVID-19 PANDEMIC - Muhammad Sajid Mehmood; Wajahat Sultan Baig; Sadia Azam Khan; Fauzia Khan; Shakil Ahmad Awan; Ayesha Babar (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: The COVID-19 pandemic has badly affected medical education. We explored the perspective of undergraduate medical students regarding e-learning across Pakistan. METHODOLOGY: A questionnaire was developed and disseminated via what’s app to MBBS students of medical institutes in Pakistan. The Google form data was retrieved in Microsoft Excel sheets and for further analysis. Ten medical colleges were selected based on a higher response rate. Out of 500 students, 492 students’ replied with valid data. SPPS-version 22 was used for data analysis. RESULTS: The mean age of respondents was 22± 2.1. 64.4% of respondents were female, and 43.6% were male. Only 5 % of total students were of the opinion that online teaching was a good substitute for learning than face-to-face sessions. Majority of the students responded that online classes were not effective. There was no statistical difference between the support offered to students by faculty and college administration before and during COVID-19. About 43% of students responded that ZOOM software was a major platform for e-learning during the lockdown. Internet connectivity (33%) was the major hurdle in e-learning, followed by distractions at home (25%). Generally, health issues (35%) and financial crises (25%) in families were major stress factors. CONCLUSION: The perspective of medical students regarding online teaching was not promising in our study. Most of the indicators were negative.